Fixed point theorems for some generalized multivalued nonexpansive mappings - Kaewcharoen A. (2014)
In this paper, we introduce a condition on multivalued mappings which is a multivalued version of condition (Cλ) defined by Garcia-Falset et al. (2011) [3]. It is shown here that some of the classical fixed point theorems for multivalued nonexpansive mappings can be extended to mappings satisfying this condition. Our results generalize the results in Lim (1974), Lami Dozo (1973), Kirk and Massa (1990), Garcia-Falset et al. (2011), Dhompongsa et al. (2009) and Abkar and Eslamian (2010) [46,3,7,8] and many others. © 2011 Elsevier Ltd. All rights reserved.